Atypical Presentation of Extraocular Sebaceous Carcinoma on The Cheek: A Case Report - Alananzh M.D, Mohammad; Abualhaj, Saleh; Alshadfan, Lina; Abuzaid, Leen; Khashram, Hasan; Arabyat, Abdallah; Alhawajreh, Dima; Massad, Basel Joseph (Journal of Neonatal Surgery, 2025)
N\A